In vitro α- glucosidase inhibitory and antioxidant activities of extract, fractions and isolated compounds from Tetracera macrophylla vall leaf - Opeyemi Roheem, Fatimah; Mat So'ad, Siti Zaiton; Ahmed, Qamar Uddin; Latip, Jalifah; Alhassan, Muhammad (2017)
Tetracera macrophylla vall. (Dilleniaceae), has been a neglected species from Tetracera genus despite its usefulness in the traditional herbal medicines. T. macrophylla leaves crude ethanol (95%) extract (ETM) and its different fractions obtained through liquid-liquid partitioning strategy were screened for their total phenolics and flavonoids contents and then investigated using in vitro models for their inhibitory activity on α-glucosidase. Free radical scavenging techniques including 2, 2diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azinobis-3-ethylbenzothiazine-6-sulfonic acid (ABTS) were used to examine the antioxidant capacity. ETM was found to be rich in both phenolic and flavonoid contents (417.90 ± 20.16, 5.86 ± 0.51 µg gallic acid (GA) and quercetin (QU) equivalent/mg dry weight) and exhibited good radical scavenging activity on DPPH and ABTS radicals ( 78.00% and 79.0%, respectively). Ethyl acetate fraction exhibited highest phenolic and flavonoid contents (206.34 ± 4.86, 14.01± 1.20 µg GA and QU equivalent/mg dry weight, respectively), and it was also observed to exhibit highest scavenging capacity on DPPH and ABTS radicals viz., 96.73%, 76.51% respectively. Both ETM and ethyl acetate fraction showed a promising and concentration-dependent α-glucosidase inhibitory activity. Bioassay guided silica gel column chromatography purification of ethyl-acetate fraction afforded a triterpenoid (12 mg), and a flavonoid (10 mg) characterized as betullinic acid and 5,7-dihydroxy-8-methoxy flavone based on spectroscopic analysis (IR, NMR). These compounds displayed promising radical scavenging activity against DPPH and ABTS radicals with moderate inhibitory activity on α-glucosidase enzymes.